2023
DOI: 10.1186/s12913-023-10026-4
|View full text |Cite
|
Sign up to set email alerts
|

“We must help them despite who they are…”: healthcare providers’ attitudes and perspectives on care for young gay, bisexual and other men who have sex with men in Nairobi, Kenya

Samuel Waweru Mwaniki,
Peter Mwenda Kaberia,
Peter Mwangi Mugo
et al.

Abstract: Background Compared to young heterosexual men, young gay, bisexual and other men who have sex with men (YMSM) face a disproportionate burden of sexual health conditions. This disparity is occasioned by factors such as criminalization and stigmatization of same-sex practices, YMSM’s limited access to non-judgmental and non-discriminatory health services, and challenges associated with healthcare delivery. We explored the attitudes and perspectives of tertiary academic institution-based healthcar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Tertiary institutions within the Nairobi metropolis have health facilities that provide care to their student population [ 24 – 26 ]. A study among HCPs drawn from some of the tertiary institution-based health facilities, demonstrated that HCPs were cognizant of their professional duty to care for YMSM [ 27 ]. However, some of the actions by HCPs such as attempts to convert YMSM to the socially acceptable heterosexual orientation [ 27 ], may have communicated hostility toward YMSM, possibly leading the latter to postpone or avoid seeking care when they needed it.…”
Section: Introductionmentioning
confidence: 99%
“…Tertiary institutions within the Nairobi metropolis have health facilities that provide care to their student population [ 24 – 26 ]. A study among HCPs drawn from some of the tertiary institution-based health facilities, demonstrated that HCPs were cognizant of their professional duty to care for YMSM [ 27 ]. However, some of the actions by HCPs such as attempts to convert YMSM to the socially acceptable heterosexual orientation [ 27 ], may have communicated hostility toward YMSM, possibly leading the latter to postpone or avoid seeking care when they needed it.…”
Section: Introductionmentioning
confidence: 99%